2020
DOI: 10.1021/acs.jpcb.9b10494
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization with Electron Decoupling in Intact Human Cells and Cell Lysates

Abstract: Dynamic nuclear polarization (DNP) is used to improve the inherently poor sensitivity of nuclear magnetic resonance spectroscopy by transferring spin polarization from electrons to nuclei. However, DNP radicals within the sample can have detrimental effects on nuclear spins close to the polarizing agent. Chirped microwave pulses and electron decoupling (eDEC) attenuate these effects in model systems, but this approach is yet to be applied to intact cells or cellular lysates. Herein, we demonstrate for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…Are we prepared for high-throughput and automatic analyses of unlabeled ECMs and carbohydrate-rich biomaterials? Could we obtain high-resolution views of the sugar components in mammalian and human cells? , How should we handle cellular mixtures like the communication and interface between microbes and plants/humans? When could we completely get rid of isotope labeling?…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Are we prepared for high-throughput and automatic analyses of unlabeled ECMs and carbohydrate-rich biomaterials? Could we obtain high-resolution views of the sugar components in mammalian and human cells? , How should we handle cellular mixtures like the communication and interface between microbes and plants/humans? When could we completely get rid of isotope labeling?…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Dynamic nuclear polarization (DNP) has emerged as a powerful method to overcome the inherent low sensitivity of nuclear magnetic resonance (NMR) spectroscopy by transferring the large polarization of unpaired electron spins to the nuclei of interest, typically 1 H. DNP provides sensitivity enhancements of 2–3 orders of magnitude, enabling the study of biomolecules and materials that are sensitivity limited and where structural studies using dipole recoupling are difficult. The success of these experiments has stimulated the sustained development of continuous-wave (CW) solid-state devices and gyrotrons that generate microwave powers ranging from several hundred milliwatts to tens of watts, respectively. In turn, these sources provide microwave irradiation to drive electron or electron–nuclear spin transitions that facilitate CW-DNP, enabling experiments at magnetic fields up to 21.1 T. …”
Section: Introductionmentioning
confidence: 99%
“…Meier et al observed acetate influx and subsequent metabolic consequences in yeast . Meier et al and Balbach et al have presented comprehensive reviews of the applications of in-cell hyperpolarized NMR. , It should be noted that solid-state in-cell DNP NMR is an emerging field. , However, only liquid-state DNP has the potential to provide information about dynamic processes such as conformational changes, reaction kinetics, and evolution of metabolite profiles in intact cells.…”
Section: Applications Of Liquid-state Dnp Nmrmentioning
confidence: 99%
“…77,78 It should be noted that solid-state in-cell DNP NMR is an emerging field. 79,80 However, only liquid-state DNP has the potential to provide information about dynamic processes such as conformational changes, reaction kinetics, and evolution of metabolite profiles in intact cells.…”
Section: Applications Of Liquid-state Dnp Nmrmentioning
confidence: 99%